2005
DOI: 10.1510/icvts.2005.109413
|View full text |Cite
|
Sign up to set email alerts
|

Histological findings induced by different energy sources in experimental atrial ablation in sheep

Abstract: The aim of this study was a detailed comparative investigation of acute cardiac alterations induced by different energy sources and approaches in a sheep model. Experiments were performed on 39 sheep. Circular lesions were created endo- or epicardially in the left atrium and at the pulmonary veins using different energy sources: cryo, microwave, laser and unipolar or bipolar radiofrequency (RF). Electrophysiological examinations were performed immediately post treatment and 2 h after ablation to prove conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 12 publications
2
25
0
2
Order By: Relevance
“…The clamping design of bipolar devices clears out heat sink due to convective cooling exerted endocardially by circulating blood, thus rendering transmurality of the lines highly predictable after both epicardial and endocardial ablation [4,8,9,21]. Temperature or impedance feedback featured by bipolar radiofrequency devices improves the reproducibility of complete tissue penetration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clamping design of bipolar devices clears out heat sink due to convective cooling exerted endocardially by circulating blood, thus rendering transmurality of the lines highly predictable after both epicardial and endocardial ablation [4,8,9,21]. Temperature or impedance feedback featured by bipolar radiofrequency devices improves the reproducibility of complete tissue penetration.…”
Section: Discussionmentioning
confidence: 99%
“…This is, on one hand, not costeffective especially in Europe where no reusable ablation device is available for cardiac use; on the other hand, ablations performed with any unipolar surgical device are not as reliably transmural as those achieved with bipolar radiofrequency [21]. In past years, we have also used a second unipolar radiofrequency device to complete the lesion set on the mitral annulus in a series of 33 patients undergoing bipolar ablation of the left atrium (control group), basically before devising a way to perform all the ablation with bipolar radiofrequency.…”
Section: Discussionmentioning
confidence: 99%
“…These changes are known to resolve after ablation, conceivably allowing a return of conduction through the gaps. Bipolar RF energy has been found to have advantages over other energy sources for surgical ablation of the atria, as it is associated with less collateral damage to surrounding structures and has the ability to indicate when the lesion has reached transmurality [4,10].…”
Section: Patient 3 (Postablation Day 18)mentioning
confidence: 99%
“…Prior studies have reported the histopathology of the human and animal atria after surgical unipolar ablation as well as percutaneous unipolar RF catheter ablation [4][5][6][7]. To our knowledge, histopathologic effects of surgical bipolar RF ablation on human atria have not been reported.…”
mentioning
confidence: 91%
“…Usage of cryoenergy is high effective, especially in atrial fibrillation correction procedures in pulmonary veins zone, but technically complicated and relatively expensive. Microwave weren't useful in clinical practice because of huge thrombogenesis, uneven endocardial lesions and high perforation rate [4] . In the 1980s, were developed and tested successfully laser ablation methodology [5,5] .…”
Section: Introductionmentioning
confidence: 99%